Immunochemical localization of ribulose-1,5-bisphosphate carboxylase in the symbiont-containing gills of Solemya velum (Bivalvia: Mollusca) - Cavanaugh, Colleen M. (1988)
The distribution of the Calvin cycle enzyme ribulose-1,5-bisphosphate carboxylase (RbuP(2)Case; EC 4.1.1.39) was examined by using two immunological methods in tissues of Solemya velum, an Atlantic coast bivalve containing putative chemoautotrophic symbionts. Antibodies elicited by the purified large subunit of RbuP(2)Case from tobacco (Nicotiana tabacum) cross-reacted on immunoblots with a protein of similar molecular mass occurring in extracts of the symbiont-containing gill tissue of S. velum. No cross-reactivity was detected in symbiont-free tissue extracts. The antiserum also cross-reacted in immunoblots with proteins of Thiobacillus neapolitanus, a free-living sulfuroxidizing chemoautotroph whose RbuP(2)Case has been well characterized. In protein A-gold immunoelectron microscopy studies, this antiserum consistently labeled the symbionts but not surrounding host gill tissue, indicating that the symbionts are responsible for the RbuP(2)Case activity.